The Function Of Sharia-Based Regional Regulations On Education And Social Services In The Regions - Achir, Nuvazria; Kamba, Sri Nanang Meiske (Universitas Negeri Gorontalo, 2021)
Through access to regional autonomy, the desire of various regions to formulate Islamic law into their laws and regulations in order to fulfill rights and obligations and respond to various problems of society becomes more open. Therefore, the purpose of this research is to reveal how the function of Sharia Regional Regulations in the implementation and fulfillment of basic service duties of local government, especially from the aspects of education and socio-culture in Gorontalo Province. This type of research includes normative legal research supported by empirical data, which examines comprehensively and analytically the primary and secondary legal materials, using statute approach and case approach. The result of the research indicates that the existence of these regional regulations is one of the provisions ensured in Law no. 23 of 2014 on Local Government and Government Regulation Number 38 of 2007 on the Division of Government Affairs, between the Provincial Government and Regency/Municipal Government. The regional regulations drafted and compiled by the Gorontalo provincial government actually assure harmony of life, security, and order. As it is in the field of one's religious education. The existence of the Regional Regulation of Reading and Writing Al-Qur'an in Gorontalo is able to embody the desire of students to develop their education to higher level, as a condition for entering the next school level. Meanwhile, from the socio-cultural aspect, the existence of Regional Regulations on the Prohibition of Gambling, Prostitution, and Liquor, helps the government create order and tranquility in people's lives, maximize regional potential and development, especially with regard to local wisdom. Therefore, the Regional Government requires to implement and maximize the provisions of sharia regional regulations in order to support development, especially those related to basic services in various aspects, in order to maximize the regional potential and local wisdom.